The link between enthesitis and arthritis in psoriatic arthritis: a switch to a vascular phenotype at insertions may play a role in arthritis development. Issue 6 (3rd August 2012) - Aydin, Sibel Z; Ash, Zoe R; Tinazzi, Ilaria; Castillo-Gallego, Concepción; Kwok, Chung; Wilson, Caroline; Goodfield, Mark; Gisondi, Paolo; Tan, Ai Lyn; Marzo-Ortega, Helena; Emery, Paul; Wakefield, Richard J; et al.
Abstract : Objective: Subclinical enthesopathy is recognised in both psoriasis and psoriatic arthritis (PsA). This study used ultrasonography with power Doppler (PD) to test the hypothesis that subclinical enthesopathy in PsA was associated with an 'inflammatory' or vascular phenotype compared to that seen in psoriasis. Methods: 100 patients with a mean age of 46.3 years (SD 15) (42 with psoriasis and 58 with PsA) and 23 matched healthy controls (HC) from two centres were included. 1230 lower limb entheses were scanned by ultrasonographers blinded to clinical details. Both inflammatory and chronic features of enthesopathy were scored. Results: Psoriasis patients (with or without arthritis) were more likely to express a vascular phenotype, with higher inflammation-related enthesopathy scores than HC (for inflammation p<0.0001, for chronicity p=0.02, for total ultrasound scores p<0.0001). The PsA patients had higher ultrasound enthesopathy scores than psoriasis patients (inflammation p=0.04, chronicity p=0.02) and HC (inflammation p<0.0001, chronicity p=0.003). When symptomatic entheses were excluded, PsA patients still had higher PD scores than psoriasis patients (p=0.003). Doppler positivity in at least one entheseal site was observed more frequently in PsA (21/58, 36.2%) versus psoriasis (4/42, 9.5%; p=0.002). Conclusions: This study shows that the ultrasound appearances of subclinical enthesitis in psoriasis differ from the subclinical enthesitis in PsA, with PsA patients having more PD. This is suggestive of a more inflammatory or vascular process in PsA, and offers potentially novel insights into the progression from skin to joint disease in psoriasis.